Standard Setting Ujian Nasional Dengan Menggunakan Metode Angoff danBookmark - Arniati Prasedyawati Herkusumo (Badan Standar, Kurikulum, dan Asesmen Pendidikan, Kemendikbudristek, 2011)
The purpose of this research is to find out the cut score of graduation for the national exam participants, as we know so far the determined passing score through judgement and the policy of the Government without paying attention to the matter of matter that exists on the test devices, and without involving the experts (as curriculum subjects teachers, expert, assessment expert). Determining graduation like this does not meet the criteria as signaled by experts such as educational measurement experts called in Standards for Educational and Psychological Testing : â€œWhen cut scores defining pass-fail, the judgmental process should be designed so that judges on bring their knowledge and experience to bear in a reasonable wayâ€. Scientific method that can be used to determine the score a passing grade is the Angoff method and bookmark method. This method can be used to determine the standard graduation test national became more scientific.Â ABSTRAKPenelitian ini bertujuan untuk mengetahui batas skor kelulusan (cut score) yang tepat bagi peserta Ujian Nasional (UN). Seperti kita ketahui bahwa sampai saat ini penentuan kelulusan pada Ujian Nasional Â ditentukan Â melalui judgement dan Â merupakan Â kebijakan Â yang Â dikeluarkan Â oleh Â Pemerintah tanpa memperhatikan soal-soal yang ada pada paket-paket UN dan tanpa melibatkan tenaga-tenaga ahli (seperti guru bidang studi, ahli kurilukum, dan ahli penilaian).Penentuan kelulusan seperti ini kurang memenuhi kriteria sebagaimana yang diisyaratkan oleh ahli-ahli pengukuran pendidikan, seperti yang disebutkan dalam Standards for Educational and Psychological Testing: â€œWhen cut scores defining passfail, the judgmental process should be designed so that judges on bring their knowledge and experience to bear in a reasonable wayâ€Metode ilmiah yang digunakan untuk menentukan standar atau cut score kelulusan pada studi ini adalah dengan menggunakan Metode Angoff dan Bookmark. Metode ini dapat digunakan untuk menentukan standar kelulusan UN menjadi lebih ilmiah.Â